1993
DOI: 10.1111/j.1365-2427.1993.tb00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic changes in surface phosphatase activity of Synedra acus (Bacillariophyceae) in relation to pH variation

Abstract: 1. The kinetics of surface phosphatase activity (PA) in the diatom Synedra acus were studied at low substrate concentrations that are frequently encountered in freshwaters and pH variations typical of hardwaters, ranging from pH 7 to pH 9. Higher pH resulted in higher values for the half saturation constant (K^,) and the maximal velodty (Vmax)-2. The pH optimum of PA was show^n to be a linear function of the logarithm of substrate concentration. 3. Similar slopes of Michaelis-Menten curves at different pHs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Hantke & Melzer (1993) found in experiments on the diatom Synedra acus that the pH optimum of APA was a linear function of the logarithm of substrate (MUFP) concentration. They obtained broad pH optima when any concentration below 0.5 jjimol 1'' of MUFP was used.…”
Section: Phosphorus Limitation Of Spring Phytoplankton 79mentioning
confidence: 98%
See 2 more Smart Citations
“…Hantke & Melzer (1993) found in experiments on the diatom Synedra acus that the pH optimum of APA was a linear function of the logarithm of substrate (MUFP) concentration. They obtained broad pH optima when any concentration below 0.5 jjimol 1'' of MUFP was used.…”
Section: Phosphorus Limitation Of Spring Phytoplankton 79mentioning
confidence: 98%
“…However, the ecological significance of the pH dependence of algal APA might vary with the alkalinity of the water and the species composition of the phytoplankton. Hantke & Melzer (1993) found in experiments on the diatom Synedra acus that the pH optimum of APA was a linear function of the logarithm of substrate (MUFP) concentration. They obtained broad pH optima when any concentration below 0.5 jjimol 1'' of MUFP was used.…”
Section: Phosphorus Limitation Of Spring Phytoplankton 79mentioning
confidence: 99%
See 1 more Smart Citation
“…Per-cell extracellular activities were generally greater at the oligotrophic site. Hantke and Melzer (1993) reported that the ability of the diatom, Synedra acus, to take up phosphate varied with pH. At low phosphate concentrations, typical of natural waters, both the half saturation constant and uptake velocity increased with increases in pH from 7 to 9.…”
Section: Ecologymentioning
confidence: 99%
“…Roloff and Nicklisch (1993) described how pH and ionic composition of humic lakes impact the movement of key nutrients such as phosphorus and iron from epilimnetic lake water into planktonic organisms. Hantke and Melzer (1993) studied the kinetics of surface phosphatase activity in the diatom, Synedra acus, at low substrate concentrations and pH variations typical of hardwaters. Bacterial and algal uptake of orthophosphate in lakes oflow trophy and during periods of phosphorous limitation were compared by Gaedke and Schweizer(1993).…”
Section: Aquatic Biotamentioning
confidence: 99%